A new method in investigation of obesity-related eating behaviors 'three-factor eating questionnaire' - GÜNEY, AHMET İLTER; KURTEL, HIZIR; ULUCAN, KORKUT; KASIMAY ÇAKIR, ÖZGÜR (AVES PRESS LTD, 2015)
Objective: TFEQ Three-factor eating questionnaire evaluates eating behaviours of individuals. In this study, it was aimed to provide the usage of this questionnaire, which was translated into Turkish and named as 'Uc Faktorlu Beslenme Anketi by verifying the validity and reliability. Methods: Fifty obese patients with a body mass index greater than 30, 50 overweight individuals with a body mass index between 25 and 30, and 50 healthy individuals with a body mass index smaller than 25 were recruited to the study. Age, gender, waist circumference, weight, height and body mass index values were recorded and the questionnaire was filled up by all individuals. Results: Reliability of the questionnaire was found to be high. In addition, it was detected that, besides the evaluation of cognitive restraint of eating, disinhibition of eating control and emotional eating, the questionnaire also evaluates susceptibility to hunger. Conclusion: Turkish version of the questionnaire could be used for the investigation of eating behaviours by other researchers in our country.
Keywords: Three-Factor Eating Questionnaire; obesity; eating behaviours